Reduction of Tannin on Red Kidney Bean, Yellow Soybean, and Black Soybean Through Peaghurt Fermentation - Fathimah Azzahra Noorhadi; Yulneriwarni; Astri Zulfa (Journal of Tropical Biodiversity, 2026)
Legumes are valuable food sources; however, their nutritional quality and utilization are often compromised by tannins, antinutrients that diminish nutrient bioavailability. Various processing methods, including soaking, boiling, germination, dehulling, roasting, and fermentation, have been applied to reduce tannin levels, with fermentation emerging as one of the most effective biological approaches. In this context, peaghurt—a novel probiotic beverage produced from fermented bean milk using lactic acid bacteria (LAB)—has gained attention due to its ability to modify physicochemical properties, including tannin content. This study assayed the efficacy of LAB starter combinations comprising Lactobacillus bulgaricus, Lactobacillus plantarum, and Streptococcus thermophilus in reducing tannin levels during peaghurt fermentation. Peaghurt was produced using a two-factor randomized block design (RBD) involving four LAB starter combinations and three bean milk substrates, each conducted in triplicate. Tannin content was quantified using UV–Vis spectrophotometry, and the data were analyzed using multivariate analysis of variance (MANOVA) followed by Tukey’s post hoc test. All LAB combinations significantly reduced tannin levels (12.79–46.18%), with the highest reduction observed in yellow soybean peaghurt fermented using the combined starter of L. bulgaricus, S. thermophilus, and L. plantarum (46.18%). This reduction is primarily ascribed to tannase activity synthesized by LAB during fermentation.